1994
DOI: 10.1111/j.0022-3646.1994.01022.x
|View full text |Cite
|
Sign up to set email alerts
|

MORPHOLOGY, PLOIDY, PIGMENT COMPOSITION, AND GENOME SIZE OF CULTURED STRAINS OFPHAEOCYSTIS(PRYMNESIOPHYCEAE)1

Abstract: We examined cell morphology, ploidy level, cell size, pigment composition, and genome size in 16 cultured strains of Phaeocystis Lagerheim. Two strains originated from the Antarctic, 3 from the tropical Western Atlantic, and 11 from temperate regions (Eastern Atlantic, English Channel, North Sea, and Mediterranean Sea). Thirteen strains made colonies morphologically similar to P. glo‐bosa Scherffel, whereas three never formed colonies under any circumstances. Five‐rayed star‐like structures with filaments were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
81
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 131 publications
(91 citation statements)
references
References 25 publications
10
81
0
Order By: Relevance
“…Vaulot et al (1994) observed 3 pigment clusters in 16 strains of Phaeocystis isolated mainly from temperate oceanic areas, supporting some of the present observations. In their Phaeocystis strains, both fucoxanthin and 19'-hexanoyloxyfucoxanthin were dominant or codominant, but 19'-butanoyloxyfucoxanthin in their study was never present except in minor or trace quantities.…”
Section: Quantitative Variation Of Chlorophyll C and Fucoxanthins Acrsupporting
confidence: 89%
“…Vaulot et al (1994) observed 3 pigment clusters in 16 strains of Phaeocystis isolated mainly from temperate oceanic areas, supporting some of the present observations. In their Phaeocystis strains, both fucoxanthin and 19'-hexanoyloxyfucoxanthin were dominant or codominant, but 19'-butanoyloxyfucoxanthin in their study was never present except in minor or trace quantities.…”
Section: Quantitative Variation Of Chlorophyll C and Fucoxanthins Acrsupporting
confidence: 89%
“…Literature ranges of chl a to marker pigment ratios used to determine the different amounts of the algal classes contributing to total chl a. See Table 1 Vaulot et al (1994), (k) Kana et al (1988), (1) Letelier et al (1993), (m) Hooks et al (1988), (n) Simon et al (1994), (0) BustillosGuzman et al (1995) and (p) Tester et al (1995) solved with the use of a least-square algorithm in order to minimise differences between chl a values observed and calculated (linear regression with constraints). This method was applied to the 72 data of chl a obtained at the 3 sampling sites.…”
Section: Methodsmentioning
confidence: 99%
“…The molecular data published to date are derived only from colonial stages or from Xagellate stages that were originally colonial. There is only a single type of ITS sequence pres- Scott and Marchant (2005), (e, h, i) from Zingone et al (1999), (b) and (g) from Vaulot et al (1994). Scale bar = 1 m on (a, b, g) Scale bar = 10 m on (c, d) Scale bar = 2 m on (e-j) Scale bar = 0.3 m on (i) ent in each strain in contrast to the multiple ITS variants in P. pouchetii and P. globosa, which strongly suggests that colonial Phaeocystis from the Antarctic are not a species complex.…”
Section: Formally Described Speciesmentioning
confidence: 99%
“…The colonies resembled those of P. globosa (Larsen and Moestrup 1989), whereas temperature tolerance was similar to that of P. pouchetii. Notably, strains from the Antarctic had diVerent pigment spectra (Buma et al 1991;Vaulot et al 1994) and DNA content . First indications that further undescribed species could exist were provided by Pienaar (1991Pienaar ( , 1996 who illustrated a Phaeocystis Xagellate with cup-shaped scales from South African waters suggesting it was a new species but not publishing a formal description.…”
Section: Introductionmentioning
confidence: 99%